2001
DOI: 10.1149/1.1403728
|View full text |Cite
|
Sign up to set email alerts
|

PEO-LiN(SO[sub 2]CF[sub 2]CF[sub 3])[sub 2] Polymer Electrolytes: I. XRD, DSC, and Ionic Conductivity Characterization

Abstract: This paper describes the preparation and characterization of poly(ethylene oxide) (PEO)-lithium bis(perfluoroethylenesulfonyl)imide (LiBETI), LiN false(SO2CF2CF3)2 polymer electrolytes. The structural properties of Pfalse(EO)n LiBETI electrolyte tapes, investigated using X-ray diffraction (XRD) and differential scanning calorimetry (DSC), are correlated with their ionic conductivities. PEO-LiBETI complexes were found to have very high ionic conductivities due to their amorphous structure. © 2001 The Electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
121
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 26 publications
9
121
0
Order By: Relevance
“…(The thermal scans were run after subjecting the samples to the same protocol adopted for obtain- ing the blue trace in Figure 2.) It is to note the plasticizing effect due to large counter ion lithium salts as LiTFSI salt, 12 leading to broader (endothermic) melting peak shifted from 65 to 59…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(The thermal scans were run after subjecting the samples to the same protocol adopted for obtain- ing the blue trace in Figure 2.) It is to note the plasticizing effect due to large counter ion lithium salts as LiTFSI salt, 12 leading to broader (endothermic) melting peak shifted from 65 to 59…”
Section: Resultsmentioning
confidence: 99%
“…From Figure 4A it is evidenced a progressive reduction of the electrolyte resistance during the initial period of storage whereas no further decrease is noticed after three days, e.g., identical bulk resistance values are found even upon very prolonged storage times (17 months). All PEO-based electrolytes (with the exception of the ionic liquid-free sample, likely due to slow crystallization kinetics of the PEO host in presence of large lithium salt counter ions) 12 exhibited analogous behavior, e.g., an initial impedance decrease followed by time-stable resistance values. This means progressive increase in conductivity (depending of the inverse of the electrolyte resistance) during the initial storage period to leveling around time-stable values.…”
Section: Resultsmentioning
confidence: 99%
“…An alternating current (AC) perturbation of 10 mV was applied to the cell. The electrolyte resistance was determined from the high frequency intercept of the impedance spectrum with the real axis and converted first to resistivity by normalizing resistance to the area and thickness of electrolyte-infiltrated monolithic 3DOM carbon, and then to ionic conductivity, the reciprocal of ionic resistivity [76,77]. …”
Section: Full Papermentioning
confidence: 99%
“…Although recent work by Zhang et al and Gadjourova at el. demonstrated that ion conduction is possible in crystalline polymers [33,34], the majority of the previous studies focused on the amorphous phase, where ion transport is dependent on the segmental motion of the polymer chains [35][36][37][38][39][40]. When lithium salts are introduced to the polymer matrix forming PEO/LiX complexes, the oxygen atoms from both the PEO chains and the anions coordinate the lithium ions [41].…”
Section: Introductionmentioning
confidence: 99%